Characterization of biomedical Ti-16Nb-(0–4)Sn alloys produced by Powder Injection Molding. (August 2017) - Yılmaz, Eren; Gökçe, Azim; Findik, Fehim; Özkan Gülsoy, H.
Abstract: Ti alloys are the most remarkable group of biomedical implant materials because of their properties such as low elastic modulus, low density, super bio-compatibility, high strength/density ratio. Metastable β-Ti alloys have lower elastic modulus compared to other types so it is possible to reduce the biomechanical mismatch and stress shielding effect of the implant-bone interfaces. Powder Injection Molding process (PIM), is an alternative method of implant production, offers some advantages such as low cost, net shape production, precise tolerances and possibility to produce complex parts simply. In this study, Ti-16Nb-XSn (X:0, 2, 4 wt%) alloys were produced through PIM method. It is observed that Sn addition has negative effect on the sintered density of the alloy when sintering process conducted at lower temperatures (1250–1400 °C) but it has no or minimum effect when sintering temperature increased to 1550 °C (96% TD). Microstructure of the emerging alloys was comprised of α + β phases, hardness of the alloys was between 4500 and 8000 MPa. Also results showed that Elastic Modulus of the Ti-16Nb alloy decreased to 77 GPa from 128 GPa by adding 2% Sn to the base alloy but it observed that no further decreasing possible by increasing amount of the Sn. Highlights: Ti-16Nb, Ti-16Nb-2Sn and Ti-16Nb-4Sn alloys produced by PIM method. Microstructural features include pores and Widmanstätten (α+β) structure. High densities (96–97%) achieved by using higher sintering temperatures. Elastic modulus of the Ti-16Nb alloy is decreased to 75–90 GPa by adding 2% wt. Sn. Elastic modulus of the alloys with Sn are lower than that of Ti6Al4V alloy.